2019
DOI: 10.1038/s41467-019-09770-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of peripheral neural circuits that regulate heart rate using optogenetic and viral vector strategies

Abstract: Heart rate is under the precise control of the autonomic nervous system. However, the wiring of peripheral neural circuits that regulate heart rate is poorly understood. Here, we develop a clearing-imaging-analysis pipeline to visualize innervation of intact hearts in 3D and employed a multi-technique approach to map parasympathetic and sympathetic neural circuits that control heart rate in mice. We identify cholinergic neurons and noradrenergic neurons in an intrinsic cardiac ganglion and the stellate ganglia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(123 citation statements)
references
References 71 publications
(108 reference statements)
2
116
1
Order By: Relevance
“…We found that B-fiber activation by VNS is related to HR drop (Fig. 4B, E), in agreement with findings in other animal studies [37,38,47]. Indeed, the vagus innervates the sinoatrial and the atrioventricular nodes, with negative chronotropic and dromotropic effects, respectively [48e50].…”
Section: Vns Evoked Fiber Activity and Physiological Responsessupporting
confidence: 91%
See 1 more Smart Citation
“…We found that B-fiber activation by VNS is related to HR drop (Fig. 4B, E), in agreement with findings in other animal studies [37,38,47]. Indeed, the vagus innervates the sinoatrial and the atrioventricular nodes, with negative chronotropic and dromotropic effects, respectively [48e50].…”
Section: Vns Evoked Fiber Activity and Physiological Responsessupporting
confidence: 91%
“…3B and C) may contribute to the cardio-inhibitory effect of VNS beyond maximum activation of Bfibers. Bradycardia can indeed be induced by selective stimulation of efferent C-fibers [52,53], whereas activation of afferent fibers, probably A-and C-type, can decrease HR by centrally enhancing parasympathetic efferent outflow and reducing sympathetic efferent outflow [47]. Finally, optogenetic activation of vagal A-and C-type afferent fibers caused bradycardia [31].…”
Section: Vns Evoked Fiber Activity and Physiological Responsesmentioning
confidence: 99%
“…Heart rate and ECG parameters were analyzed in response to vagal photostimulation in ChAT-ChR2 transgenic mice (expressing the ChR2 opsin in cholinergic, and thus parasympathetic axons). With 473nm illumination at the left cervical vagus nerve, as expected 44,45 , heart rate was reduced substantially from baseline during stimulation and returned to baseline following the stimulus (-54%, p=8.1e-37) (Figure 2A). The Q-T interval also decreased significantly (-43%, p=8.0e-26), along with P-wave amplitude (-26%, p=4.3e-9) and T-wave amplitude (-13%, p=2.1e-13), while the P-R interval increased during stimulation (+5%, p=9.2e-12)(Figure2A&B).…”
Section: One-photon Cervical Photostimulation In Chat-chr2 Transgenicmentioning
confidence: 55%
“…The stellate ganglia, which contain the cell bodies of sympathetic neurons that predominantly innervate the heart 1 , are of considerable interest to cardiovascular research 2 . Surgical removal of these ganglia is being used with great success clinically to treat life threatening ventricular arrhythmias associated with structural heart disease and some inherited arrhythmia syndromes 2,3 .…”
Section: Introductionmentioning
confidence: 99%